Human rights and climate change - Humphreys, Stephen, 1971-; Robinson, Mary, 1944-; Cambridge eBooks (Cambridge : Cambridge University Press, 2010)
As the effects of climate change continue to be felt, appreciation of its future transformational impact on numerous areas of public law and policy is set to grow. Among these, human rights concerns are particularly acute. They include forced mass migration, increased disease incidence and strain on healthcare systems, threatened food and water security, the disappearance and degradation of shelter, land, livelihoods and cultures, and the threat of conflict. This inquiry into the human rights dimensions of climate change looks beyond potential impacts to examine the questions raised by climate change policies: accountability for extraterritorial harms; constructing reliable enforcement mechanisms; assessing redistributional outcomes; and allocating burdens, benefits, rights and duties among perpetrators and victims, both public and private. The book examines a range of so-far unexplored theoretical and practical concerns that international law and other scholars and policy-framers will find increasingly difficult to ignore.
Introduction: Human rights and climate change / Stephen Humphreys -- Competing claims : human rights and climate harms / Stephen Humphreys -- Climate change, human rights and moral thresholds / Simon Caney -- Equitable utilization of the atmosphere : a rights-based approach to climate change? / Dinah Shelton -- Climate change, human rights and corporate accountability / Peter Newell -- Rethinking human rights : the impact of climate change on the dominant discourse / Sam Adelman -- The Kyoto Protocol and vulnerability : human rights and equity dimensions / Philippe Cullet -- Forests, climate change and human rights : managing risks and trade-offs / Frances Seymour -- Climate change and the right to the highest attainable standard of health / Paul Hunt and Rajat Khosla -- Human rights and vulnerability to climate change / Jon Barnett -- Climate change, evolution of disasters and inequality / John C. Mutter and Kye Mesa Barnard -- Conceiving justice : articulating common causes in distinct regimes / Stephen Humphreys.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Human rights; Climatic changes -- Law and legislation; Global warming -- Law and legislation; Climatic changes -- Political aspects -- Developing countries; Electronic books